I assume you're talking about a fraction,
(2<em>i</em> ²⁰ + <em>i</em> ⁴²) / (<em>i</em> ¹⁰¹ - <em>i</em> ²)
Remember that <em>i</em> ² = -1; from this it follows that
<em>i</em> ³ = <em>i</em> ² × <em>i</em> = -<em>i</em>
<em>i</em> ⁴ = <em>i</em> ³ × <em>i</em> = (-<em>i </em>) × <em>i</em> = -<em>i </em>² = -(-1) = 1
<em>i</em> ⁵ = <em>i</em> ⁴ × <em>i</em> = <em>i</em>
<em>i</em> ⁶ = <em>i</em> ⁵ × <em>i</em> = <em>i</em> ² = -1
and so on. In particular, raising <em>i</em> to some integer multiple of 4 reduces to 1.
Using the above pattern, we find
<em>i</em> ²⁰ = 1
<em>i</em> ⁴² = <em>i</em> ⁴⁰ × <em>i</em> ² = 1 × (-1) = -1
<em>i</em> ¹⁰¹ = <em>i</em> ¹⁰⁰ × <em>i</em> = 1 × <em>i</em> = <em>i</em>
So, we have
(2<em>i</em> ²⁰ + <em>i</em> ⁴²) / (<em>i</em> ¹⁰¹ - <em>i</em> ²) = (2 - 1) / (<em>i</em> - (-1)) = 1 / (<em>i</em> + 1)
We can stop here, but usually it's more useful to have complex numbers written in standard <em>a</em> + <em>bi</em> form. To get this result, multiply the numerator and denominator by the complex conjugate of <em>i</em> + 1:
(2<em>i</em> ²⁰ + <em>i</em> ⁴²) / (<em>i</em> ¹⁰¹ - <em>i</em> ²) = 1 / (<em>i</em> + 1) × (-<em>i</em> + 1) / (-<em>i</em> + 1)
… = (-<em>i</em> + 1) / (-<em>i</em> ² + 1²)
… = (-<em>i</em> + 1) / (-(-1) + 1)
… = (1 - <em>i</em> ) / 2
or equivalently,
… = 1/2 - 1/2 <em>i</em>